Research on the Propagation Law of Fire Smoke on the Working Face of a Belt Conveyor - Yinshang Wei; Anquan Li; Yi Li; Wei Liang (Fire)
In view of the spread and distribution of high-temperature toxic smoke on the working face during belt conveyor fires, the FDS was used to carry out numerical simulation, establish a belt conveyor fire simulation model, set up a variety of working conditions, and study the flue gas spread of the working face with different ignition source locations and different heat release rates. The results show that the flue gas reaching the working face varies greatly from different ignition source locations, and the smoke propagation time of the working face decreases first and then increases with the increase in the scale of the fire. The location of the fire source is from 0 to 700 m, and the visibility of the working face will drop to less than 3 m within 10 min, which seriously affects emergency evacuation; the maximum concentration of CO in the working face is proportional to the heat release rate, the fire source is less than 100 m away from the working face, and the temperature of the air inlet area of the working face is higher than 60 °C, which poses a great threat to personnel evacuation. When the fire source is less than 200 m away from the working face, the evacuees will encounter smoke damage on the working face, and when the fire scale reaches 4 MW and 6 MW, the CO concentration will have a great impact on the evacuation and make people incapacitated.